2003
DOI: 10.1002/marc.200390036
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Alkylaluminium Activators and Mixtures thereof on Ethylene Polymerization with a Tridentate Bis(imino)pyridinyliron Complex

Abstract: The effect of various alkylaluminium compounds and their mixtures on ethylene polymerization catalyzed with a tridentate bis(imino)pyridinyliron catalyst is studied. Triethylaluminium and trihexylaluminium are good cocatalysts but yield polyethylenes with broad molar mass distribution (MMD) whereas triisobutylaluminium, a less efficient activator, gives polyethylenes with unimodal and narrow MMD. Specific mixtures of branched and linear alkylaluminium compounds yield highly active catalytic systems and polyeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 10 publications
1
29
0
1
Order By: Relevance
“…Notably, the polyethylene obtained using Al( i -Bu) 3 as the co-catalyst displayed a relatively narrow and unimodal molecular weight distribution [116] . By mixing AlMe 3 with Al( i -Bu) 3 the catalytic activity was found to be higher than that obtained by taking each activator individually [117] . Using the tetraethylaluminoxane, Et 2 AlOAlEt 2, in combination with 5a the activity of the catalyst is higher than using AlEt 3 or Al( i -Bu) 3 [118] .…”
Section: Other Co-catalysts/activatorsmentioning
confidence: 95%
See 1 more Smart Citation
“…Notably, the polyethylene obtained using Al( i -Bu) 3 as the co-catalyst displayed a relatively narrow and unimodal molecular weight distribution [116] . By mixing AlMe 3 with Al( i -Bu) 3 the catalytic activity was found to be higher than that obtained by taking each activator individually [117] . Using the tetraethylaluminoxane, Et 2 AlOAlEt 2, in combination with 5a the activity of the catalyst is higher than using AlEt 3 or Al( i -Bu) 3 [118] .…”
Section: Other Co-catalysts/activatorsmentioning
confidence: 95%
“…A similar bimodal molecular weight distribution containing large fractions of low molar mass products can be obtained using 5a in combination with AlMe 3 [116,117] . On studying a range of trialkylaluminiums as activators it was found that the catalytic activity followed the order AlMe 3 < Al( n -Oct) 3 < Al( i -Bu) 3 < AlEt 3 < Al( n -Hex) 3 , with MAO-based systems still displaying the highest activity.…”
Section: Other Co-catalysts/activatorsmentioning
confidence: 96%
“…Recently, it was reported that common alkylaluminum compounds, such as triethylaluminum (AlEt 3 ), tri-iso-butylaluminum (Al(i-Bu) 3 ) and so on, were also very effective in ethylene polymerization with a nickel-based complex [4]. The alkylaluminum compounds or aluminoxanes acted as chain transfer agents and therefore affected the molecular weights and molecular weight distributions of polymers [5][6][7]. However, the active species for these iron(II) catalytic systems were not as well understood as those for the ␣-diimine nickel and palladium catalytic systems [8].…”
Section: Introductionmentioning
confidence: 99%
“…[1,5,7] In ref. [9][10][11][12][13] it was shown that instead of MAO aluminum trialkyls [AlMe 3 , Al(i-Bu) 3 , etc.] can be used for efficient activation of LFeCl 2 complexes, and activity of the catalysts LFeCl 2 /AlR 3 was close to that of LFeCl 2 /MAO system.…”
Section: Introductionmentioning
confidence: 99%